Exchange Rate Regime Choice - Marion, Nancy; Flood, Robert (Washington, D.C. : International Monetary Fund, 1991)
Traditionally the choice of exchange rate regime has been seen as a second-best policy choice, which can be directed toward mitigating the distortionary effects of price or information rigidities. In this paradigm the optimal degree of exchange rate flexibility is found to depend of the source and nature of shocks hitting an economy. More recent literature views the exchange rate as a widely and frequently seen manifestation of government policy with careful exchange-rate management emerging as a tool that can enhance shaky policy credibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet